An RNA-based fluorescent biosensor for high-throughput analysis of the cGAS-cGAMP-STING pathway - Bose, Debojit (Cell Chem Biol, 2016)
In mammalian cells, the second messenger (2′-5′, 3′-5′) cyclic GMP-AMP (2′, 3′-cGAMP), is produced by the cytosolic DNA sensor cGAMP synthase (cGAS), and subsequently bound by stimulator of interferon genes (STING) to trigger interferon response. Thus, the cGAS-cGAMP-STING pathway plays a critical role in pathogen detection, as well as pathophysiological conditions including cancer and autoimmune disorders. However, studying and targeting this immune signaling pathway has been challenging due to the absence of tools for high-throughput analysis. We have engineered an RNA-based fluorescent biosensor that responds to 2′, 3′-cGAMP. The resulting “mix-and-go” cGAS activity assay shows excellent statistical reliability as a high-throughput screening (HTS) assay and distinguishes between direct and indirect cGAS inhibitors. Furthermore, the biosensor enables quantitation of 2′, 3′-cGAMP in mammalian cell lysates. We envision this biosensor-based assay as a resource to study the cGAS-cGAMP-STING pathway in the context of infectious diseases, cancer immunotherapy, and autoimmune diseases.